Characteristics Of Children Mother Who Have Preeklamsia In Bulukumba Regency - Kurniati, Ely; Sari, Iramaya (Jurnal Life Birth, 2017)
Childbirth is an important process for a mother. In the process of childbirth naturally the mother will spend a lot of energy and experience changes both physiologically and psychologically. Data obtained in the 2016 Medical Record total maternity of 1589 there were 132 cases of maternity women who experienced preeclampsia which were divided into 36 cases of mild preeclampsia, 36 cases of severe preeclampsia and 90 cases of eclampsia. The formulation of the problem in this study is "What are the characteristics of maternal women who have preeclampsia in H.A. Hospital Sulthan Daeng Radja, Bulukumba Regency, 2016 . The purpose of this research is to determine the classification of maternal women who have preeclampsia at H.A Sulthan Daeng Radja Hospital in Bulukumba Regency in terms of age, parity and gestational age. The design of this study uses quantitative descriptive. The study design uses quantitative descriptive, research time in August, and conducted at H.A Sulthan Daeng Radja Hospital, a population and sample of 132 cases. by using total sampling techniques, research instruments using the register of maternity rooms. Based on the results of research conducted classification of respondents based on the type of preeclampsia most experienced severe preeclampsia (PEB). Characteristics of respondents based on the age of mothers who experienced preeclampsia mostly included in the category of low risk (20-35 years), Characteristics of respondents based on parity of women who experienced preeclampsia were mostly included in the primiparous category, Characteristics of respondents based on gestational age who experienced preeclampsia were mostly included in the category Atter